Hifz al-Bi’ah sebagai Maqashid Syariah Kontemporer: Analisis Konseptual terhadap Legitimasi Green Sukuk dalam Pengelolaan Dana Haji di Indonesia - Rara Genta Munggarani Basri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The management of Hajj funds in Indonesia requires the application of sharia principles that not only maintain financial security, but also sustainable benefits. Green sukuk emerged as an investment instrument that combines sharia principles with environmentally friendly financing. However, the legitimacy of green sukuk from the perspective of Maqashid Sharia, especially related to environmental protection (hifz al-bi'ah), is still rarely studied systematically. This study aims to analyze the position of hifz al-bi'ah as a contemporary Maqashid and assess the legitimacy of green sukuk in the management of Hajj funds in Indonesia. The method used is qualitative normative-conceptual through literature studies, with data from Maqashid Sharia literature, DSN-MUI fatwas, policy documents, and publications related to green sukuk. The descriptive-qualitative analysis shows that hifz al-bi'ah can be positioned as a contemporary Maqashid that strengthens the legitimacy of green sukuk, so that this instrument is not only Sharia-compliant, but also supports the sustainable management of Hajj funds and is aligned with the principle of public benefit.